Development of a new atmospheric pressure plasmaspray ionization for ambient mass spectrometry. (6th August 2020) - Peng, Zhen; Liu, Ji‐Xing; Zhu, Hui; Guo, Teng; Xu, Li; Dong, Jun‐Guo; Cheng, Ping; Zhou, Zhen
Abstract: A new atmospheric pressure ionization method, plasmaspray ionization, termed as PSI, was developed to be an alternative ambient ion source for mass spectrometry. It comprises a plasma jet device and a sample spray part. While the nonthermal plasma jet strikes the surface of stainless steel tube out of the spray capillary, the sprayed sample will be ionized with the assistant of auxiliary gas. Although PSI is a little bit more complex than electrospray ionization (ESI) in instrument, it shows both better linearity and higher sensitivity for organic compounds. For protein samples, it presents wider distributions of multiply charged ions and higher mass resolution without sacrificing any sensitivity. For the mechanism of PSI, the charge build‐up process on the tip of capillary should play a key role for the ion formation, and the stimulated pulsed voltage on the flow tube will promote the ion aggregation speed until the charge density is high enough. PSI source contains the features of plasma ionization and ESI and can be considered as a novel combo bridging these techniques. These results reflect that this method of PSI can be applied and further developed as a versatile new ion source for a wild range of organic and biological samples.